Prospect of Modification Treatment and Application of Natural Zeolite Materials - Li , Yan; Lu, Nan (Scientific Journal of Technology, 2025)
The efficient and extensive utilization of natural zeolites is restricted by factors such as pore blockage, weak ion exchange selectivity, and small adsorption capacity. Modifying natural zeolite materials is an important means to enhance their performance and value. Based on existing research results, this paper summarizes the characteristics of inorganic treatment, thermal modification, organic modification, metal loading and composite modification of zeolite materials, as well as their main applicable conditions and influencing factors. Finally, it looks forward to the challenges of large-scale production and application of modified natural zeolites, and proposes to strengthen research and practice in green and efficient modification processes, new functional targeted modification, intelligent manufacturing and application monitoring, etc., to provide scientific references for the high-value utilization of natural zeolite resources.